Human interface and the management of information. 17th International Conference, HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings /: 17th International Conference, HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings. Information and knowledge in context : Part II, (2015) - Unknown
No abstract available